EFFECT OF CLIMATE CHANGE ON ANNUAL WATER ALLOCATION PLAN - Sutapa, I Wayan; Arafat, Yassir; Lipu, Sance; Rustiati, Nina Bariroh (Journal of Applied Engineering Science, 2022)
The most felt impact due to climate change in Indonesia is the climate anomaly. This condition will affect the planning of water allocation. The purpose of this study was to determine the impact of climate change on the annual water allocation plan. This research was conducted in the Bangga watershed, Indonesia. The methods used include climate change detection, irrigation water needs, domestic and non-domestic water needs, water availability, water balance, and an annual water allocation plan. The data used is daily rainfall data for 29 years (1993-2021) from Bangga Atas and Bangga Bawah stations and climate data from Bora station for the same period. The results of this study are: there has been a change in climate in the Bangga watershed and there has been an increase in rainfall in the last 10 years so the availability of water has also increased. Climate change has a very big influence on the availability of rivers, especially in the dry year, causing a water deficit. This condition applies to the period 1995-2021. In normal year conditions and wet year conditions, there is a change in the status of the water balance from deficit to surplus for the last 10 years. The annual water allocation plan based on the period 2012-2021 is proposed as an annual water allocation plan for the next five years and can be reviewed after three years. Meanwhile, the strategy to reduce the water shortage deficit is to make a priority scale for all water needs.
Keywords: climate change, water balance, water allocation annual plan, Bangga watershed